Prioritizing involuntary immobility in climate policy and disaster planning - Lisa Thalheimer; Fabien Cottier; Andrew Kruczkiewicz; Carolynne Hultquist; Cascade Tuholske; Hélène Benveniste; Jan Freihardt; Mona Hemmati; Pui Man Kam; Narcisa G. Pricope; Jamon Van Den Hoek; Andrew Zimmer; et al. (Nature Communications)
Abstract Globally, populations are increasingly located in areas at high risk of climate change impacts. Some populations lack the agency to move out of harm’s way, leading to involuntary immobility. The climate risks these populations face are insufficiently addressed in climate policy and disaster planning. While policy and planning should be data-informed, the lack of appropriate data should not limit governments and institutions from taking action to reduce the risk of involuntary immobility. Incorporating involuntary immobility within the broader sustainable development goals of climate action and safe, orderly, and regular migration may substantially reduce the risk of involuntary immobility.